PEMERIKSAAN ZAT WARNA MERAH PADA MINUMAN BOTOL YANG BEREDAR DI SEKITAR JALAN KAPTEN MUSLIM MEDAN SECARA KROMATOGRAFI KERTAS - Yosy Cinthya Eriwaty Silalahi; Dicky Yuswardi Wiratma; Artha Yuliana Sianipar (UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Drinks are materials that are needed by living things, which are useful for survival. Therefore, many manufacturers are innovating with drinks, one of which is bottled drinks and adding colorants to drinks to attract buyers. The purpose of this study was to determine whether or not the use of red dye is not allowed in bottled drinks sold around Jalan Captain Muslim Medan. This study uses a descriptive method, namely by conducting examinations in the laboratory. Drinks that are red were taken as samples, namely as many as 5 samples. Samples were purified using wool absorption, followed by identification using paper chromatography compared with tables. The results of the observations showed that from the 5 samples tested, none of the bottled drinks containing red dye were prohibited.